SATISFACTION ANALYSIS OF TWO - ACCOUNT HOLDER’S CUSTOMER (SAVINGS OF SHARIAH BANKS AND CONVENTIONAL BANKS) - Aulia, Dita Siti Juharina (Al-Infaq: Jurnal Ekonomi Islam, 2017)
This study attempts to analyze the customer‟s satisfaction and preference of banking services. Characteristics of respondents are a customer holding savings accounts in Islamic banks and conventional banks. The method used to analyze customer satisfaction is the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA).The method will produce how satisfied customers who have accounts in Islamic and conventional banks. Meanwhile, to measure the client's preferences is using Analytical Hierarchy Process (AHP). This method would be known to the client's preferences in using banking services, be it Islamic or conventional banks. The results showed that customer satisfaction in Islamic banks is 72.03%, while customer satisfaction conventional bank is 73.11%. Customerpreferences in selecting Islamic banks are 48% while customer preferences in selecting conventional banks are 49%. Based on the research, satisfaction and customer preference is still higher in the conventional banks than in Islamic banks. This also shows that there are still many people who have the mindset of a rational economic interest even though they are aware that the bank has elements which are not good in religion or economically in the long term.